Femme Fragile in Slovene Literature at the Turn of the 20th Century - Čeh Steger, Jožica (Slavia Centralis, 2023)
The present paper focuses on the literary type called femme fragile at the turn of the 20th century. In this period, the femme fragile both in visual arts and in literature experiences a rich development and some changes. She is shaped in accordance with the aesthetic guidelines of decadence, the secession and symbolism; she echoes medical and other discourses about femininity, male views of the female and the fear of increasing female independence. The analysis of the femme fragile in selected works of Slovene modernism reveals that the authors adjusted her also to social circumstances. The Slovene femme fragile is not a representative of the aristocracy. She originates from the bourgeois, or even rural, environment, and her origins might reach as far as to the folklore Fair or Lepa Vida.
Keywords: discourse about femininity, femme fragile, Ivan Cankar, Izidor Cankar, Fran Govekar, Alojz Kraigher